Amplifying Dynamic Nuclear Polarization of Frozen Solutions by Incorporating Dielectric Particles - Kubicki, Dominik J. (J Am Chem Soc, 2014)
[Image: see text] There is currently great interest in understanding the limits on NMR signal enhancements provided by dynamic nuclear polarization (DNP), and in particular if the theoretical maximum enhancements can be achieved. We show that over a 2-fold improvement in cross-effect DNP enhancements can be achieved in MAS experiments on frozen solutions by simply incorporating solid particles into the sample. At 9.4 T and ∼105 K, enhancements up to ε(H) = 515 are obtained in this way, corresponding to 78% of the theoretical maximum. We also underline that degassing of the sample is important to achieve highest enhancements. We link the amplification effect to the dielectric properties of the solid material, which probably gives rise to scattering, diffraction, and amplification of the microwave field in the sample. This is substantiated by simulations of microwave propagation. A reduction in sample heating at a given microwave power also likely occurs due to reduced dielectric loss. Simulations indicate that the microwave field (and thus the DNP enhancement) is inhomogeneous in the sample, and we deduce that in these experiments between 5 and 10% of the solution actually yields the theoretical maximum signal enhancement of 658. The effect is demonstrated for a variety of particles added to both aqueous and organic biradical solutions.